Food markets in Banke, Nepal: Retail shop characteristics - Bi, Afrin Zainab; Gupta, Ishika; Mahida, Darshanaben; Isanovic, Sejla; Boncyk, Morgan; Kabir, A.N.M. Faijul; Choudhury, Samira; Veettil, Prakashan Chellattan (CGIAR System Organization, 2023)
The Transforming Agrifood Systems in South Asia (TAFSSA) district agrifood systems assessment aims to provide a reliable, accessible, and integrated evidence base that links farm production, market access, dietary patterns, climate risk responses, and natural resource management in Bangladesh, India, Nepal, and Pakistan. It is designed to be a multi-year assessment. Using data collected in February–March 2023, this brief describes which food items are available and their prices, characteristics of retail shops, markets, and customers, as well asmarketing and promotional activities. It is one of a set of briefs that, together, provide a holistic picture of the food system in the district.